1999
DOI: 10.1515/jpem.1999.12.3.381
|View full text |Cite
|
Sign up to set email alerts
|

gps Mutations in Chilean Patients Harboring Growth Hormone-Secreting Pituitary Tumors

Abstract: Hypersecretion of GH is usually caused by a pituitary adenoma and about 40% of these tumors exhibit missense gsp mutations in Arg201 or Gln227 of the Gs, gene. We studied 20 pituitary tumors obtained from patients with GH hypersecretion. One tumor was resected from an 11 year-old boy with a 3 year history of accelerated growth, associated with increased concentrations of serum GH and IGF-I, which were not suppressed by glucose administration. The remaining 19 tumors were obtained from adult acromegalic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
2
14
1
2
Order By: Relevance
“…Regarding the somatotropinomas, the prevalence of gsp we found is lower than the expected 40%, considering previous series from several countries in the literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The reason for such a low prevalence in our series is unknown.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Regarding the somatotropinomas, the prevalence of gsp we found is lower than the expected 40%, considering previous series from several countries in the literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The reason for such a low prevalence in our series is unknown.…”
Section: Discussioncontrasting
confidence: 59%
“…The finding that our gsp+ patients had higher tumor diameter than gsp-patients is not in accordance with the previously described in the literature. The previous series evidenced that gsp+ tumors were smaller [7,13,17,19] or not different in size [11,12,16] from the gsp-tumors. However, in only three of our gsp+ patients the information of the tumor diameter was available, making our finding difficult to be taken into account at this point.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Patients in the mutation positive group went to surgery with smaller tumors and had lower GH levels. 22 Other studies found lower, 23 higher 24,25 or the same GH levels in the mutation positive group. [26][27][28][29][30][31][32] G-protein mutations occur frequently in somatotrophs, 25 and tumors carrying these mutations are more susceptible to inhibition of GH secretion by somatostatin analogs, such as octreotide.…”
Section: Mccune-albright Syndrome (Mas)mentioning
confidence: 86%